The Beginnings of Translation Studies - St-Pierre, Paul (TTR)

(untitled) (Association canadienne de traductologie, 2017)
It was in the 1970s that the object of study in literature departments began to change, under the impetus of novel approaches, some radically new and others renewed forms of older ones—structuralism, semiotics, intertextuality, psychoanalysis, pragmatics, deconstruction, reader-response theory, hermeneutics, discourse analysis, etc. Many (but not all) of these were French in origin, at least in part: the names of Lévi-Strauss, Barthes, Kristeva, Lacan, Derrida, Ricoeur, Foucault can be cited. And along with the change in the definition of the object of study came a change in the way literature departments defined themselves and their role. This is clear from the way department of literatures renamed themselves and introduced new programs. These changes came about at different times in different places, dependent in good part on the amount of access that existed to the publications—many of which were in French—but especially to the debates they gave rise to. It was in this context of expansion and of redefinition—presented here in terms of my own particular history—that an interest in translation, and later in Translation Studies, developed. Of course, translation was not an entirely new object of study; linguists and students of literature (especially of comparative literature) had on occasion acknowledged its existence, and even at times, its importance. However, it was only with the advent of the new approaches to texts, to reading, to interpretation, and to the context of the transmission of meaning(s) and of expression, that a conception of the importance of translation, and of its interest from a theoretical point of view, was able to develop. This led, in the 1980s, to the construction of a new discipline—Translation Studies.